Kamienne dziedzictwo wczesnopiastowskiej architektury - Skoczylas, Janusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
In the article I draw attention to the lack of consistency in descriptions of the rock material used to build the first structures in the early Piast state. The role and importance of the types of stone material used at that time are unappreciated, if not downright ignored. I emphasize the fact that the main material used in early-medieval building construction were glacial erratics, sometimes representing up to 98% of the entire building material. Other rocks used in constructing buildings included travertine, sod iron ore, limestone and  gypsum. However, I have devoted a lot of attention to the Miocene quartzite sandstone excavated in the early stages of Polish statehood from a quarry in Brzeźno near Konin. In the summary, I suggest possible time scales for the use of part of the rock material.